Mark-recapture estimates of seasonal abundance and survivorship for bottlenose dolphins (Tursiops truncatus) near Charleston, South Carolina, USA - Speakman, Todd R.; Lane , Suzanne M.; Schwacke, Lori H.; Fair , Patricia A.; Zolman , Eric S. (J. Cetacean Res. Manage., 2023)
The stock structure of western North Atlantic bottlenose dolphins (Tursiops truncatus) is complex, with seasonally migratory stocks often overlapping with year-round resident stocks. High rates of exchange between northernmost sites have been documented but movement and seasonal fluctuation in abundance among sites along the southern portion of the US Atlantic coast is not well understood. To better understand seasonal abundance, a three-year mark-recapture study of bottlenose dolphins in coastal and estuarine waters near Charleston, South Carolina, USA was conducted. A robust design was employed in order to minimise bias and more precisely determine seasonal estimates of abundance and concurrently examine temporary immigration/emigration and survivorship. Systematic boat-based surveys were carried out (n = 192) from January 2004 to December 2006. The entire study area was surveyed one week per month; an additional survey was conducted in the months in which seasonal abundance was estimated: January (winter), April (spring), July (summer) and October (autumn). Standard photo-identification techniques were used to accumulate sightings of 521 distinctively marked dolphins, 65% of which were sighted more than once. Pollock’s robust design was applied using MARK and the ensuing abundance estimates were adjusted for the seasonal proportion of unmarked dolphins (ranging from 0.27 to 0.40) in the population. Estimates ranged from 364 (95% CI = 305–442) in January 2004 to 910 (95% CI = 819–1018) in October 2006. Summer abundance estimates were consistently greater than those from winter months, although estimates varied considerably among years. The same model was used to calculate an annual survival rate estimate of 0.951 (95% CI = 0.882–1.00) for marked individuals within the population. A high degree of transience, demonstrated by seasonal influxes of single-sighted individuals, made it difficult to differentiate between mortality and permanent emigration. The results support the occurrence of three distinct dolphin groups found in Charleston waters: year-round residents; seasonal residents; and transients. Reporting abundance and survivorship estimates together is useful in explaining and validating results for populations in which transient individuals occur. These results provide important information for stock and viability assessment of coastal bottlenose dolphins in the western North Atlantic.